Synergistic effect of co-digestion to enhance anaerobic degradation of catering waste and orange peel for biogas production. Issue 9 (September 2017) - Anjum, Muzammil; Khalid, Azeem; Qadeer, Samia; Miandad, Rashid
Catering waste and orange peel were co-digested using an anaerobic digestion process. Orange peel is difficult to degrade anaerobically due to the presence of antimicrobial agents such as limonene. The present study aimed to examine the feasibility of anaerobic co-digestion of catering waste with orange peel to provide the optimum nutrient balance with reduced inhibitory effects of orange peel. Batch experiments were conducted using catering waste as a potential substrate mixed in varying ratios (20–50%) with orange peel. Similar ratios were followed using green vegetable waste as co-substrate. The results showed that the highest organic matter degradation (49%) was achieved with co-digestion of catering waste and orange peel at a 50% mixing ratio (CF4). Similarly, the soluble chemical oxygen demand (sCOD) was increased by 51% and reached its maximum value (9040 mg l -1 ) due to conversion of organic matter from insoluble to soluble form. Biogas production was increased by 1.5 times in CF4 where accumulative biogas was 89.61 m 3 t -1 substrate compared with 57.35 m 3 t -1 substrate in the control after 80 days. The main reason behind the improved biogas production and degradation is the dilution of inhibitory factors (limonene), with subsequent provision of balanced nutrients in the co-digestion system. The tCOD of the final digestate was decreased by 79.9% in CF4, which was quite high as compared with 68.3% for the control. Overall, this study revealed that orange peel waste is a highly feasible co-substrate for anaerobic digestion with catering waste for enhanced biogas production.